Барабан і «складне оро» – аналіз міфосимволічного й обрядового значення - Чаусидис, Н. (Народна творчість та етнографія, 2009)
In this article we reach the mytho-symbolic and ritual character of the drum considering the Macedonian (and broadely the Balkan) traditional culture. We summarize its role in the shamanic activities, afterwards assuming its role as the mystical «mean of transportation», which in the scope of the Macedonian dance «Teškoto» enable the dance leader to separate himself from the earth and its traveling to the «other world». There is an atempt the component of the mystical travel to be found in the dancing on one leg (typical for the «Teškoto» dance) and especially in relation with the appropriate pose of the stork / crane as a paradigmatic zoomorphyc traveler between the worlds. The comparative research shows that the drummer often carries within itself the priest functions. Regarding the way of the performing (kicking/hiting) he is also considered as blacksmith and magician. In the Macedonian traditional culture the both functions were accomplished by the foreigners (most frequently the gypsies - blacksmiths). This thesis is focused on one archeological object discoverеd in Suvodol (near Bitola) representing an animal (horse) head carved in a stone. Its analogies could be traced through the East Europe up to the Caspian coast, and to be connected with the influences and migrations of the Indo-Europeans during the 3rd millennium B.C. We present the hypothesis strasing that this object had sacral caracter with several functions: ruler scepter, drum percussion and magical instrument. All these components emphasize the sacralised animal (horse) as the mediator which was the main factor for achieving the already mentioned functions. At the end we consider the relation between the hiting in the drum, stroke of the thunder, the drummer and the God of Tunder.